MXenes as emerging nanomaterials in water purification and environmental remediation - Yu, Shujun; Tang, Hao; Zhang, Di; Wang, Shuqin; Qiu, Muqing; Song, Gang; Fu, Dong; Hu, Baowei; Wang, Xiangke (The Science of the total environment, 2022)
Environmental pollution has accelerated and intensified because of the acceleration of industrialization, therefore fabricating excellent materials to remove hazardous pollutants has become inevitable. MXenes as emerging transition metal nitrides, carbides or carbonitrides with high conductivity, hydrophilicity, excellent structural stability, and versatile surface chemistry, become ideal candidates for water purification and environmental remediation. Particularly, MXenes reveal excellent sorption capability and efficient reduction performance for various contaminants of wastewater. In this regard, a comprehensive understanding of the removal behaviors of MXene-based nanomaterials is necessary to explain how they remove various pollutants in water. The eliminate process of MXene-based nanomaterials is collectively influenced by the physicochemical properties of the materials themselves and the chemical properties of different contaminants. Therefore, in this review paper, the synthesis strategies and properties of MXene-based nanomaterials are briefly introduced. Then, the chemical properties, removal behaviors and interaction mechanisms of heavy metal ions, radionuclides, and organic pollutants by MXene-based nanomaterials are highlighted. The overview also emphasizes associated toxicity, secondary contamination, the challenges, and prospects of the MXene-based nanomaterials in the applications of water treatment. This review can supply valuable ideas for fabricating versatile MXene nanomaterials in eliminating water pollution. [Display omitted] •The developmental timeline of MXenes for water treatment is summarized.•The synthesis strategies and characteristics of MXenes are introduced.•The removal behaviors of heavy metals, radionuclides, and organics are determined.•The removal mechanisms are electrostatic, coordination, and catalytic degradation.•MXenes with abundant terminal functional groups show excellent performance.